Choice predicts the feedback negativity. (28th July 2017) - McGill, Stuart; Buckley, Jude; Elliffe, Douglas; Corballis, Paul M.
Abstract: Choosing the appropriate response given the circumstance is integral to all aspects of human behavior. One way of elucidating the mechanisms of choice is to relate behavior to neural correlates. Electrophysiological evidence implicates the ERP feedback‐negativity (FN) and the P300 as promising neural correlates of reward processing, an integral component of learning. However, prior research has not adequately addressed how the development of a preference to select one option over another (choice preference) relates to the FN and the P300. We assessed whether variation in choice preference predicted the FN and P300 amplitude within subjects. We used a discrete‐trials two‐alternative choice procedure, where the reinforcer rate for each option was dependently scheduled by a concurrent variable interval. The reinforcer ratio for selecting each option was varied between sessions. Choice was quantified using both the generalized matching law sensitivity and the log odds of staying on the same versus switching to the other alternative (stay preference). The relationship between stay preference, FN, and P300 amplitudes was assessed using the innovative application of hierarchical Bayesian linear regression. The results demonstrate that stay preference was controlled by the reinforcer ratios and credibly predicted the FN amplitude but not P300 amplitude. The findings are consistent with the view that reinforcers may guide behavior by what they signal about future reinforcement, with the FN related to such a process.